Van Canh Triassic granite in the Kontum Massif, central Vietnam: Geochemistry, geochronology, and tectonic implications. Issue 7 (1st June 2022) - Hung, Doan Dinh; Tsutsumi, Yukiyasu; Hieu, Pham Trung; Minh, Nguyen Trung; Minh, Pham; Dung, Nguyen Thi; Hung, Nguyen Ba; Komatsu, Toshifumi; Hoang, Nguyen; Kawaguchi, Kenta
Graphical abstract: Highlights: The S-type Van Canh pluton in southern Kontum Massif is composed of med- to high-K. The Van Canh pluton was derived by melting of Paleoproterozoic crustal rocks. The pluton was formed by the continental collision during the Early Triassic. Abstract: The Kontum Massif, located in central Vietnam, played an essential role in the evolution of Indochina and its adjacent areas. The Van Canh granites, exposed throughout the Southern Kontum Massif, display SiO2 contents ranging from 65.82 to 75.35 wt%, and total alkaline (Na2 O + K2 O) from 5.47 to 9.82 wt%, with A/CNK values between 0.97 and 1.08. The main rock-forming minerals of the Van Canh granites are quartz (25–30 vol%), K-feldspar (27–30 vol%), plagioclase (28–30 vol%), and biotite (3–5 vol%). The whole-rock chemical composition is characterized by Ba, Nb, Ce, P, and Ti- depletion, and the enrichment of Th, K, Pb, Nd, and Y. The ɛHf(t) values of zircon grains range from −11.1 to −6.7, and the Hf model ages (TDM2 ) are from 1.97 to 1.70 Ga. Their geochemical features are similar to the S-type granite, being derived from partial melting of Paleoproterozoic sources. The zircon Hf model ages and inherited zircon ages are evidence of Paleoproterozoic basement in the study region. LA-ICP-MS zircon U-Pb dating yields crystallization ages of 251–229 Ma, showing the existence of Triassic magmatism in the Kontum Massif. The Van Canh granites in the Kontum Massif, central Vietnam, provide significant evidence for the syn-/post-collision of North Vietnam-South China and Indochina blocks.